PROBLEMATIKA PELAKSANAAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN TERHADAP PERJANJIAN KERJA WAKTU TERTENTU DI PT. GRAHA MANDALA SAKTI - Edi Hartono (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACTEdi Hartono. "Problems in the Implementation of Law Number 13 Year 2003 concerning Employment Against Certain Time Work Agreements at PT. Graha Mandala Sakti "under the guidance of Ms. Isnawati, SH., M.H as I and Mr. Dr. H. Ismail, SH., M. Hum as II counselorWork agreement is one form of agreement to carry out work as referred to in Article 1601 of the Civil Code. In Article 50 of Law Number 13 of 2003 concerning Manpower, it is stated that labor relations occur because of the existence of work agreements between employers and workers / laborers. Specific Time Work Agreement (PKWT) is a work agreement that has a validity period determined or referred to as a contract employee.The purpose of this study is to find out how the implementation of a certain time work agreement (PKWT) at PT. Graha Mandala Sakti. The type of research used in this study is empirical research where this research is carried out by looking at and gathering all information related to the reality in the implementation of practice in the field.The results of this study are the application of a certain time work agreement (PKWT) in work relations at PT. Graha Mandala Sakti has not been effective in accordance with applicable regulations. The company has ignored the maximum deadline permitted by Law Number 13 of 2013 concerning Labor concerning the period of PKWT. The first factor is that most types and characteristics of the work needed are jobs that are included in the core work of the production process and are permanent and the second factor is the omission of the provisions of the PKWT in employment relations, which according to the authors are caused by very loose government oversight of the reality on the ground. Keywords: Implementation of PKWT